Proceedings of the 2014 Conference on Designing Interactive Systems 2014
DOI: 10.1145/2598510.2598573
|View full text |Cite
|
Sign up to set email alerts
|

The design space of shape-changing interfaces

Abstract: Technologies for shape-changing user interfaces are rapidly evolving, but our understanding of the design space of such interfaces is still limited. We report a repertory grid study that aims to describe the design space from the users' point of view by eliciting personal constructs about shapechange. The study is based on six similar-sized, shapechanging artifacts that combine simple sensing of users with actuation that change volume, texture, and orientation. Our results show that the 18 respondents distingu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 33 publications
0
26
0
Order By: Relevance
“…They also analyze the toys to refine interaction properties of shape-changing interfaces. Kwak et al [26] reported a repertory grid study that aims to describe the shape change features from the users' point of view by eliciting personal constructs about shape-change and focusing on understanding the feeling generated by different deformations. Rasmussen et al [44] presented an analysis of sketches made by designers, focusing on a radio and a mobile phone, and, using on Rasmussen et al taxonomy, they show which features are most often used in general or for certain devices (e.g., Spatiality used only for radio, Adding/Subtracting used only for mobile phone).…”
Section: Taxonomy On Shape-changing Interfacesmentioning
confidence: 99%
See 2 more Smart Citations
“…They also analyze the toys to refine interaction properties of shape-changing interfaces. Kwak et al [26] reported a repertory grid study that aims to describe the shape change features from the users' point of view by eliciting personal constructs about shape-change and focusing on understanding the feeling generated by different deformations. Rasmussen et al [44] presented an analysis of sketches made by designers, focusing on a radio and a mobile phone, and, using on Rasmussen et al taxonomy, they show which features are most often used in general or for certain devices (e.g., Spatiality used only for radio, Adding/Subtracting used only for mobile phone).…”
Section: Taxonomy On Shape-changing Interfacesmentioning
confidence: 99%
“…Shape-changing interface taxonomies [4,43,46] help describe the reconfigurability of interfaces and can be used to design new interfaces [26,35,44,52]. To date, there has been little effort to unify and strengthen these taxonomies despite shape changing interfaces continuously evolving.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Where the modular approach "grows" through addition, the shape change approach is self-contained and changes shape under computational control: an interactive node could present new, rich action possibilities in response to "growth" of the systems. That our students are not alone in seeing this is clear from the abundance of literature on the subject (e.g., [31][32][33]). …”
Section: Shape Changing Approachmentioning
confidence: 99%
“…Sturdee et al (2016) employed a participatory design process which showcased a shape-changing prototyping tool in order to gain perspectives on the desires for this new technology from a public participant base. There are also a growing number of papers which examine the deeper implications of this technology, such as emotionality (Kwak et al 2014) and temporality (Vallgarda, 2007).…”
Section: Introductionmentioning
confidence: 99%